Urethra-preserving and dorsal capsule fenestration with robot-assisted simple prostatectomy for severe LUTS in small prostate: a case report - Wen, Lijie; Zhang, Yue; He, Yi; Yu, Yang; Yang, Bo (Frontiers in Surgery, 2024)
BackgroundSmall prostates (volume <30 ml) induce bladder outlet obstruction with pathophysiological changes distinct from those associated with large prostates. Treatment options often include transurethral incision of the prostate (TUIP) or transurethral resection of the prostate (TURP). Existing treatments have issues with high recurrence and complication rates. Therefore, we aim to explore a new minimally invasive surgical approach for patients with severe lower urinary tract symptoms (LUTS) and a small prostate.MethodsA patient with severe LUTS and a small prostate was admitted to the Department of Urology at the Second Hospital of Dalian Medical University. The patient had no median lobe but presented with multiple bladder stones. Relevant data (IPSS score, urine flow rate, operation time, hemoglobin drop, catheterization time, hospitalization time, residual urine) were collected before and after surgery to assess the safety and efficiency.ResultsThe patient was 72 years old with a prostate volume of 22.14 ml, a preoperative IPSS score of 28, PSA of 0.314 ng/ml, maximum urine flow rate of 3.5 ml/s, and a prostate MRI PI-RADS score of 2. The patient underwent robot-assisted cystolithotomy, urethra-preserving prostatectomy and dorsal capsule fenestration. The surgery lasted 105 min, with a postoperative hemoglobin drop of 3 g/L. There was no continuous bladder irrigation postoperatively, and the catheter was removed after 10 days. The patient was hospitalized for 4 days and followed up for 24 months. At 6 months postoperative, the patient had an IPSS score of 6, a QoL score of 1, a urine flow rate of 18 ml/s, and residual urine of 8 ml, with nocturia occurring 1–2 times. At 24 months postoperative, the patient had an IPSS score of 7, a QoL score of 1, a urine flow rate of 21 ml/s, and residual urine of 15 ml, with nocturia occurring 1 time.ConclusionRobot-assisted urethra-preserving prostatectomy and dorsal capsule fenestration is a promising alternative treatment for patient with severe LUTS due to a small prostate in both long-term safety and efficacy. Further large-sample controlled studies are needed for additional evaluation and validation.